Pelaksanaan Promosi pada UMKM Mawar Batik Kecamatan Salem Kabupaten Brebes - Ramadhani; Gunawan, Rachmat (Jurnal Riset Manajemen dan Akuntansi, 2026)
This study aims to analyze the implementation of promotional activities at Mawar Batik MSME located in Salem District, Brebes Regency. The study is motivated by the limited application of digital advertising and direct marketing, which has resulted in restricted promotional reach and product information delivery. This research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation conducted during the Field Work Practice (Kuliah Kerja Lapangan). The findings indicate that promotional activities were previously dominated by direct selling, while digital promotion was characterized by inconsistent content uploads, simple visual presentation, and limited utilization of digital platforms. During the field work activities, initial promotional improvements were implemented through the use of social media, content organization, the development of a simple product catalog, and enhanced communication with customers both directly and digitally. Although these efforts are still at an early stage, they have begun to increase business visibility and customer interaction. The study concludes that combining consistent digital advertising with personalized direct marketing is essential to expand market reach, strengthen product appeal, and support the sustainability of batik MSMEs.